Claiming and Making Muslim Worlds Religion and Society in the Context of the Global - Dağyeli, Jeanine Elif; Ghrawi, Claudia; Freitag, Ulrike (ZMO-Studien, 2021)
This volume explores what 'Islam' is taken to mean in different social, economic and cultural contexts. It considers how people engage and employ varying traditions, institutions, and media in shaping their sense of self and place. It also investigates how competing notions of 'Islam' intersect with questions of governance. The book complicates neat conventional divisions and invites to think across disciplines and in translocal contexts.